Nonunion of the Pisiform Bone in a 9-Year-Old Boy. (June 2015) - Brouwers, Lars; Hannemann, Pascal F. W.; Brink, Peter. R. G.
Abstract An isolated fracture of the pisiform bone is a rare condition, especially in children. The fracture may be missed in the emergency department because of the complex anatomy of the carpal region. Early diagnosis and treatment are, however, important for the functional outcome of the patient, since untreated dislocated carpal fractures may result in nonunion. We report one case of a 9-year-old boy with an unrecognized fracture of the pisiform bone who underwent a pisiformectomy 10 months after injury due to a nonunion of the pisiform bone. Good results were obtained and the wrist did not show any functional impairment.